Social harmony at work: A sharedness index linking team atmosphere to individual well-being in a Japanese company - Kazuhiro Ito; Shoko Wakamiya; Masae Manabe; Yasushi Watanabe; Masataka Nakayama; Yukiko Uchida; Eiji Aramaki (PLoS ONE, 2025)
Social harmony, defined as the flourishing of interdependent relationships, is central to well-being in workplace teams but is often measured with abstract self-reports that offer limited interpretability and limited guidance for interventions. This study aims to operationalize social harmony as an interpretable sharedness index and to test its association with individual well-being. In a two-month field study at a Japanese company, 94 employees from 23 teams submitted daily reports containing an 11-point well-being score, an 11-point team atmosphere score, and a short diary entry. We computed two weekly team level indices. The score-based sharedness index was defined as the negative of the within team standard deviation of team atmosphere scores. The text-based sharedness index was defined as the mean semantic similarity among members weekly concatenated diaries using Word Mover’s Distance. Across team weeks, score-based sharedness correlated positively with mean individual well-being (r = 0.332, p = 0.0002), and text-based sharedness showed a weaker but significant correlation (r = 0.257, p = 0.003). Convergent validity with social harmony was indicated by team level associations with the Interdependent Happiness Scale (score-based r = 0.66, p = 0.019; text-based r = 0.44, p = 0.086). These findings suggest that sharedness reflects a practically interpretable component of social harmony in workplace teams and is positively associated with individual well-being, although causal and intervention effects remain to be tested. The index can be computed from routine ratings and diaries, which supports its use for monitoring and for designing interventions to promote employee well-being.